2009
DOI: 10.1089/neu.2008.0523
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Contusion Causes Acute Plasma Membrane Damage

Abstract: Spinal cord injury (SCI) launches a complex cascade of events that leads to progressive damage and loss of function. Compromise of plasma membrane integrity due to the mechanical impact is an acute event that may contribute to cellular dysfunction. Therefore, the objective of this study was to better understand the extent of acute plasma membrane damage associated with SCI as a function of injury severity and membrane defect size. Fluorescent cell-impermeant dyes were injected into the cerebrospinal fluid of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 59 publications
4
33
0
1
Order By: Relevance
“…One possible reason that 4-AP only partially restores conduction is that some of the axons that suffered myelin damage also suffered axonal membrane disruption, compromising the integrity of both structures which are indispensible in neuronal function. In support of such a notion, there is widespread membrane damage following spinal cord mechanical trauma (Shi, 2004;Simon et al, 2009), and compounds that are known to seal membrane disruption, such as polyethylene glycol, can also restore axonal conduction (Donaldson et al, 2002;Shi and Borgens, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason that 4-AP only partially restores conduction is that some of the axons that suffered myelin damage also suffered axonal membrane disruption, compromising the integrity of both structures which are indispensible in neuronal function. In support of such a notion, there is widespread membrane damage following spinal cord mechanical trauma (Shi, 2004;Simon et al, 2009), and compounds that are known to seal membrane disruption, such as polyethylene glycol, can also restore axonal conduction (Donaldson et al, 2002;Shi and Borgens, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since CNS cells are not adapted to such forces and deformations, they are vulnerable to dysfunction and death at insult levels that other cells may survive. The devastating sequelae following neural injury is caused not only by the physical deformation of the tissue and structural failure such as membrane damage (Singleton and Povlishock, 2004;Farkas et al, 2006;Whalen et al, 2007;Simon et al, 2009), but also with secondary complications such as inflammation, altered cellular signaling, and changes in gene expression (Gaetz, 2004;Raghupathi, 2004). These complications are thought to be mediated by mass depolarization and release of excitatory amino acids (e.g., glutamate) that can, in turn, activate cell death pathways (Colicos and Dash, 1996;Conti et al, 1998) and phenomena such as post-traumatic epileptogenesis (Teasell et al, 2007).…”
Section: Neuropathology Of Traumatic Injurymentioning
confidence: 99%
“…Mechanoporation is particularly important in mild to moderate TBI, in which widespread cell death is absent, yet functional deficits are evident (Povlishock and Christman, 1995;McAllister et al, 2001), preserving the opportunity for reparative interventions. An increase in neuronal plasma membrane permeability has been recognized as one of the earliest biophysical events observed after experimental in vivo traumatic CNS injury (Pettus et al, 1994;Povlishock and Pettus, 1996;Borgens and Shi, 2000;Shi, 2004;Choo et al, 2007;Whalen et al, 2007;Simon et al, 2009). From a functional standpoint, studies have shown that plasma membrane damage is associated with conduction block (Shi and Whitebone, 2006), aberrant cell signaling (Serbest et al, 2006), protease activation (Farkas et al, 2006), alterations in cellular morphology Stone et al, 2001), and delayed cell death (Whalen et al, 2007).…”
Section: The Role Of the Plasma Membrane In The Initial Mechanical Rementioning
confidence: 99%
“…Additional studies are hence needed to determine if this is a generic feature in cell compression experiments, which could be useful since culture compression experiments that induce PM tension and thereby increase PM permeability are highly relevant in pressure ulcer and chronic wound research (Slomka et al, 2009). The permeability of the PM of deformed cells to fluorescent markers such as propidium iodide, Lucifer yellow or fluorescein-conjugated dextran of different molecular sizes may be a useful indirect measure of the level of tensional PM strains, as recently demonstrated by Simon et al (2009).…”
Section: Discussionmentioning
confidence: 99%